White matter abnormalities in major depressive disorder with melancholic and atypical features: A diffusion tensor imaging study. Issue 6 (29th December 2014) - Ota, Miho; Noda, Takamasa; Sato, Noriko; Hattori, Kotaro; Hori, Hiroaki; Sasayama, Daimei; Teraishi, Toshiya; Nagashima, Anna; Obu, Satoko; Higuchi, Teruhiko; Kunugi, Hiroshi
<x xml:space="preserve">Abstract</x> Aim The DSM‐IV recognizes some subtypes of major depressive disorder (MDD). It is known that the effectiveness of antidepressants differs among the MDD subtypes, and thus the differentiation of the subtypes is important. However, little is known as to structural brain changes in MDD with atypical features (aMDD) in comparison with MDD with melancholic features (mMDD), which prompted us to examine possible differences in white matter integrity assessed with diffusion tensor imaging (DTI) between these two subtypes. Methods Subjects were 21 patients with mMDD, 24 with aMDD, and 37 age‐ and sex‐matched healthy volunteers whose DTI data were obtained by 1.5 tesla magnetic resonance imaging. We compared fractional anisotropy and mean diffusivity value derived from DTI data on a voxel‐by‐voxel basis among the two diagnostic groups and healthy subjects. Results There were significant decreases of fractional anisotropy and increases of mean diffusivity in patients with MDD compared with healthy subjects in the corpus callosum, inferior fronto‐occipital fasciculus, and left superior longitudinal fasciculus. However, we detected no significant difference in any brain region between mMDD and aMDD. Conclusion Our results suggest that patients with MDD had reduced white matter integrity in some regions; however, there was no major difference between aMDD and mMDD.